Minimal residual disease detection in pediatric acute myeloid leukemia: does flow cytometry score a point over molecular biology? - Venditti, Adriano; Del Principe, Maria Ilaria; Maurillo, Luca; Buccisano, Francesco; Amadori, Sergio (Translational Pediatrics, 2012)
In acute myeloid leukemia (AML), achievement of morphologic complete remission (RC) still remains the “gold standard” to make a judgment on treatment response and yet hematologists wonder about its utility in the era of minimal residual disease (MRD) detection.